2019
DOI: 10.1111/jcpe.13100
|View full text |Cite
|
Sign up to set email alerts
|

Industry sponsorship bias in clinical trials in implant dentistry: Systematic review and meta‐regression

Abstract: Aim: Industry sponsorship might distort the conduct and findings of studies in a large range of medical disciplines. The objective of this study was to assess whether industry sponsorship bias is present in randomized controlled trials (RCTs) on dental implants. Material and methods:Two databases were searched (MEDLINE; Web of Science) to identify RCTs published between 1996 and 2016 assessing different implant systems, components or techniques, such as implant-abutment connections, geometries, surfaces, loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 29 publications
2
36
1
Order By: Relevance
“…We also observed that industry‐sponsored trials had greater chance of presenting some sort of selective reporting, which is in agreement with other reports (van den Bogert et al., ; Popelut, Valet, Fromentin, Thomas, & Bouchard, ; Wayant et al., ). A recent review, however, could not verify association of sponsorship with marginal bone loss, which is an outcome frequently used in implant trials (Dos Santos, Agostini, de Moraes, Schwendicke, & Sarkis‐Onofre, ).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that industry‐sponsored trials had greater chance of presenting some sort of selective reporting, which is in agreement with other reports (van den Bogert et al., ; Popelut, Valet, Fromentin, Thomas, & Bouchard, ; Wayant et al., ). A recent review, however, could not verify association of sponsorship with marginal bone loss, which is an outcome frequently used in implant trials (Dos Santos, Agostini, de Moraes, Schwendicke, & Sarkis‐Onofre, ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the impact of the involvement of industries in oral implantology is not clear (Barao et al., 2012; Dos Santos, Agostini, de Moraes, Schwendicke, & Sarkis‐Onofre, 2019). Our results failed to draw a conclusion on whether studies funded by industries received higher AAS.…”
Section: Discussionmentioning
confidence: 99%
“…For researchers, having external funding is a reflection of self‐capacity and could avoid financial problems during the research. In addition, it was reported that no significant sponsor bias was identified in RCTs on oral implantology and that the quality of funded research could be relied on in clinical decision making (Dos Santos et al., 2019). However, when a product is promoted on the Internet, its beneficial effect could be magnified, while the methodological aspects, veracity and accuracy of information, and adverse events could be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…A COI occurs when professional judgment about a primary interest is overly influenced by a secondary interest such as financial gain. Randomized controlled trials (RCTs) in which authors have some type of COI are more likely to support the intervention being assessed (Popelut et al 2010; Brignardello-Petersen et al 2013), although this pattern was not consistent across all studies (Yuan et al 2011; Dos Santos et al 2019). Despite the attempts of the International Committee of Medical Journal Editors (ICMJE) to promote uniform and transparent reporting of conflicts of interest, journal adoption remains suboptimal (Holden and Spallek 2018).…”
Section: Discussionmentioning
confidence: 99%